Structural and spatial chromatin features at developmental gene loci in human pluripotent stem cells - Hiroki Ikeda; Masamitsu Sone; Shinya Yamanaka; Takuya Yamamoto (Nature Communications, 2017)
Higher-order chromatin organization regulates the expression of transcriptional programs that control cell function. Here, the authors show that chromatin interaction profiles and nuclear positions at developmental gene loci differ between human somatic and pluripotent stem cells.